IMPLEMENTASI 12 BALANCE EXERCISE UNTUK MEMPERTAHANKAN KESEIMBANGAN POSTURAL PADA LANSIA DENGAN PENYAKIT RHEUMATOIDARTHRITIS (RA) DI UPT PELAYANAN SOSIAL LANJUT USIA BINJAI - Elvinna, Yulvi; Olivia, Nina; Pratama, Muchti Yuda (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
ABSTRACT Rheumatoid Arthritis (RA) is a chronic autoimmune disease that causes joint inflammation and is commonly experienced by the elderly. This condition affects body balance and increases the risk of falls. One non-pharmacological method to improve postural balance is the application of the 12 Balance Exercise. This exercise aims to strengthen the lower extremity muscles and enhance the function of the vestibular system. This study used a descriptive case study method with a nursing care approach. starting from assessment. nursing diagnosis, implementation, and evaluation. involving two elderly patients with RA who had postural balance disturbances. The intervention applied was the 12 Balance Exercise for two weeks with a frequency of three times per week. Each session lasted 15 minutes and was evaluated using the Berg Balance Scale (BBS). After six intervention sessions, the results showed an improvement in postural balance scores in both patients, shifting from a moderate fall-risk category to a low fall-risk category. The patients demonstrated better ability to stand and walk without assistance. This study concludes that the application of the 12 Balance Exercise is effective in improving postural balance among elderly patients with RA and reducing the risk of falls. The implementation of the 12 Balance Exercise can be used as part of nursing interventions and a standard approach for elderly individuals with balance disorders due to RA in geriatrie care units ABSTRAK Rheumatoid Arthritis (RA) adalah penyakit autoimun kronis yang menyebabkan peradangan pada sendi dan sering dialami oleh lansia. Kondisi ini dapat mengganggu keseimbangan postural dan meningkatkan resiko jatuh. Salah satu metode non-farmakologis untuk meningkatkan keseimbangan postural adalah dengan penerapan 12 Balance Exercise. Latihan ini bertujuan memperkuat otot ekstremits bawah dan sistem vestibular. Metode penelitian ini merupakan studi kasus deskriptif pada dua lansia penderita RA dengan gangguan keseimbangan postural di UPT pelayanan Sosial Lanjut Usia Binjai. Intervensi yang diberikan adalah 12 Balance Exercise selama dua minggu dengan frekuensi tiga kali perminggu. Setiap sesi latihan dilakukan selama 15 menit dan dinilai dengan menggunakan Berg Balance Scale (BBS). Hasil penelitian ini setelah dilakukan intervensi selama dua minggu, terjadi peningkatan skor keseimbangan postural pada kedua pasien, dari kategori resiko jatuh sedang menjadi resiko jatuh rendah. Pasien menunjukan kemampuan yang lebih baik dalam berdiri dan berjalan tanpa bantuan. Kesimpulan dari penerapan 12 Balance Exercise efektif dalam menngkatkan keseimbangan postural pada lansia dengan RA serta menurunkan resiko jatuh. Saran penelitian ini latihan 12 Balance Exercise dapat dijadikan sebagai bagian dari intervensi keperawatan standar untuk lansia dengan gangguan keseimbangan akibat RA di unit pelayanan lanjut usia.